2007
DOI: 10.1177/0148607107031004284
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Catheter‐Related Bloodstream Infections in Parenteral Nutrition Catheterization

Abstract: It was concluded that the duration of catheterization should be shortened; that the intravascular catheter, which is inserted in urgent situations, should be removed as soon as possible; and that maximal sterile barrier precautions should be taken and due attention should be paid to hand hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 21 publications
6
71
1
3
Order By: Relevance
“…Perform hand hygiene before catheter insertion or manipulation (B-II). [30][31][32][33] a. Use an alcohol-based waterless product or antiseptic soap and water.…”
Section: Infrastructure Requirementsmentioning
confidence: 99%
“…Perform hand hygiene before catheter insertion or manipulation (B-II). [30][31][32][33] a. Use an alcohol-based waterless product or antiseptic soap and water.…”
Section: Infrastructure Requirementsmentioning
confidence: 99%
“…In a previous study performed in our hospital evaluating total parenteral nutrition catheters, Yilmaz et al identified coagulasenegative staphylococci as the most common agent, followed by S. aureus, P. aeruginosa, and Acinetobacter spp., with a level of 3.2% for Enterococcus spp. (19). The high MRSA and E. faecalis levels in our study may be explained by greater staphylococcal and enterococcal colonization due to the advanced age of our patients.…”
Section: Discussionmentioning
confidence: 57%
“…Asimismo, Aguilella 17 observó que existe un aumento del riesgo de infección a medida que aumenta el número de días, puesto que primero se produce la colonización del CVC y luego la bacteriemia, lo que sugiere un tiempo de latencia antes de manifestarse clínicamente la infección; esto coincide con nuestros resultados ya que existe una correlación de Pearson positiva entre el número de dias de exposición y el porcentaje de ITS. De esta manera, nuestros datos sugieren que limitar la duración de la NPT es una forma de prevenir las ITS/CVC y que se deben asegurar esfuerzos para evaluar periódicamente el posible cambio a nutrición enteral 18 . Artículo Original…”
Section: Discussionunclassified